Development and testing of two methods for the measurement of the mowing machine feed rate - F. Kumhála; M. Kroulík; J. Mašek; V. Prošek (Plant, Soil and Environment, 2003)
Two methods were developed and tested for the measurement of the mowing machine material feed rate (based on the conditioner power input measured by a torque-meter, and/or on the material change in momentum measured by a curved impact plate). The measurements carried out in the year 2001 proved that a very good linear relationship existed between the conditioner power input, output frequency of the apparatus measuring the impact force by means of the impact plate, and the material feed rate through the mowing machine. The calculated R-Squared values were about 0.95. In the year 2002, the impacts of material and condition (parameters) changes on the mowing machine material feed rate measurement accuracy were measured under laboratory conditions. It was evident from the statistical evaluation that changing crop variety, crop maturity, and intensity of conditioning can have a statistically significant influence on the measurement based on the torque-meter. As concerns the impact plate measurement, it was found that it is not possible on the basis of our measurements to determine statistically the influence of the factors tested.